2017
DOI: 10.1037/dev0000355
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ body image trajectories: A further test of the self-equilibrium hypothesis.

Abstract: The self-equilibrium hypothesis underlines the importance of having a strong core self, which is defined as a high and developmentally stable self-concept. This study tested this hypothesis in relation to body image (BI) trajectories in a sample of 1,006 adolescents (Mage = 12.6, including 541 males and 465 females) across a 4-year period. The results supported the self-equilibrium hypothesis among 3 profiles of adolescents, all characterized by matching BI levels and stability: (a) High (48.0%); (b) Increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 170 publications
(328 reference statements)
2
13
0
Order By: Relevance
“…This model of sociocultural influences has been well supported in longitudinal studies of adolescent girls and boys (Field et al, 2001; Paxton, Eisenberg, & Neumark-Sztainer, 2006). Consistent with the tripartite influence model, subgroups who exhibit different body image trajectories have been shown to vary in terms of appearance-related teasing (Rodgers et al, 2016; Wang et al, 2019), relationships with peers and parents (Morin et al, 2017; Wang et al, 2019), internalization of cultural appearance ideals, and engagement in appearance comparisons (Rodgers et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This model of sociocultural influences has been well supported in longitudinal studies of adolescent girls and boys (Field et al, 2001; Paxton, Eisenberg, & Neumark-Sztainer, 2006). Consistent with the tripartite influence model, subgroups who exhibit different body image trajectories have been shown to vary in terms of appearance-related teasing (Rodgers et al, 2016; Wang et al, 2019), relationships with peers and parents (Morin et al, 2017; Wang et al, 2019), internalization of cultural appearance ideals, and engagement in appearance comparisons (Rodgers et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
“…For example, Nelson, Kling, Wangqvist, Frisen, and Syed (2018) identified three trajectories of appearance esteem from age 10 to 24 years: high and relatively stable (53%), moderate early adolescent decline (36%), and steep early adolescent decline (11%). Examining girls' and boys' perceptions of their own physical attractiveness between ages 12 and 16 years, Morin, Maiano, Scalas, Janosz, and Litalien (2017) identified three trajectories: high (48.0%), increasing (34.1%), and decreasing (17.9%) perceived attractiveness. Studies that have applied similar analyses to the construct of body dissatisfaction have also found evidence for multiple developmental trajectories between ages 15 and 31 years (Wang et al, 2019), and specifically in girls throughout early adolescence (Rodgers, McLean, Marques, Dunstan, & Paxton, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In later development, there was a transactional association between peer victimization and body dissatisfaction that was only present in girls, which supported our hypothesis that effects would be stronger in girls than boys. There are several possible explanations for this, in that compared to boys, body dissatisfaction tends to be higher among girls (Morin et al., ), girls are more likely to receive weight‐based teasing from peers and family members, and teasing from multiple sources translates into greater risk of emotional dysfunction (Eisenberg, Neumark‐Sztainer, & Story, ). Lastly, our measure of body dissatisfaction mostly tapped into weight, and while this is a prominent feature of body dissatisfaction among girls, boys are typically orientated toward muscularity (Karazsia, Murnen, & Tylka, ); it is possible that pubertal development led to increased concern about muscle size or strength in boys, particularly those maltreated by their peers (Haltigan & Vaillancourt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, rates of overweight and obesity tend to be equally distributed among girls and boys (Ng et al., ; Ogden et al., ). Despite comparable rates of exposure, the consequences of excess adiposity (Booth et al., ; Griffiths, Wolke, Page, & Horwood, ; Mustillo et al., ) and peer victimization (Copeland, Wolke, Angold, & Costello, ; Hoglund, ) such as poorer academic, social, and psychiatric outcomes, appear to be stronger among girls than boys, and body dissatisfaction tends to be higher among girls and women compared to boys and men (Morin, Maïano, Scalas, Janosz, & Litalien, ). An examination of moderating effects is therefore warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, results from this study generally indicated that more variance was explained in the weight management behaviors than in the body image outcomes. This makes sense because, although one's body image can be changed, self-concept is particularly stable (Morin, Scalas, Maïano, Janosz, & Litalien, 2017). Behaviors, on the other hand, are more concrete (something a person either does or does not do) and can therefore be more easily influenced.…”
Section: Rq2: Weight Management and Body Image Outcomesmentioning
confidence: 99%